Seeing People and Seeing God: Rethinking the Active and Contemplative Lives in Thomas Malory's Morte Darthur - Pierce, Ingrid (Journal of medieval religious cultures, 2024)
It has been observed that Thomas Malory's Morte Darthur exhibits the active and contemplative lives much discussed in medieval England as modes of Christian living. However, no one has yet explored how Malory examines the lives by foregrounding sight, which in the Morte is vital to action and contemplation. Sight brings people into relation with one another and with God but it can also mesmerize minds and overwhelm bodies. This article argues that Malory stresses the need to educate the sense of sight and better understand visual connection. His portrayal of seeing helps elucidate medieval England's evolving models of sense perception and religious life.